2018
DOI: 10.1111/tpj.14060
|View full text |Cite
|
Sign up to set email alerts
|

Application of phiLOV2.1 as a fluorescent marker for visualization of Agrobacterium effector protein translocation

Abstract: Agrobacterium tumefaciens can genetically transform plants by translocating a piece of oncogenic DNA, called T-DNA, into host cells. Transfer is mediated by a type IV secretion system (T4SS). Besides the T-DNA, which is transferred in a single-stranded form and at its 5' end covalently bound to VirD2, several other effector proteins (VirE2, VirE3, VirD5, and VirF) are translocated into the host cells. The fate and function of the translocated proteins inside the host cell are only partly known. Therefore, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
1
8
0
1
Order By: Relevance
“…The protoplasts were imaged 16 h later using confocal microscopy (Supplementary Figure 1). Consistent with data from previous studies (Bhattacharjee et al, 2008;Grange et al, 2008;Lee et al, 2008;Li et al, 2014Li et al, , 2020Shi et al, 2014;Li and Pan, 2017;Lapham et al, 2018;Roushan et al, 2018), VirE2-Venus localized to the cytoplasm (Supplementary Figure 1A); however, VirE2-Venus-NLS localized to the nucleus (Supplementary Figure 1B). Although we have not precisely identified where in the cytoplasm VirE2-Venus localizes, it does not localize to the nucleus, and for convenience we shall hereafter refer to the subcellular localization of VirE2-Venus as "cytoplasmic.…”
Section: Cytoplasmic But Not Nuclear Localized Vire2 Can Support Transformationsupporting
confidence: 91%
See 1 more Smart Citation
“…The protoplasts were imaged 16 h later using confocal microscopy (Supplementary Figure 1). Consistent with data from previous studies (Bhattacharjee et al, 2008;Grange et al, 2008;Lee et al, 2008;Li et al, 2014Li et al, , 2020Shi et al, 2014;Li and Pan, 2017;Lapham et al, 2018;Roushan et al, 2018), VirE2-Venus localized to the cytoplasm (Supplementary Figure 1A); however, VirE2-Venus-NLS localized to the nucleus (Supplementary Figure 1B). Although we have not precisely identified where in the cytoplasm VirE2-Venus localizes, it does not localize to the nucleus, and for convenience we shall hereafter refer to the subcellular localization of VirE2-Venus as "cytoplasmic.…”
Section: Cytoplasmic But Not Nuclear Localized Vire2 Can Support Transformationsupporting
confidence: 91%
“…In the plant cell, VirE2-GFP complexes formed filamentous structures mainly in the cytoplasm and with a few that appeared within the nucleus. Roushan et al (2018) used phiLOV2.1 to tag VirE2 internally and showed that, when transferred from Agrobacterium, the protein localized to the cytoplasm of Arabidopsis roots and Nicotiana tabacum leaves. Li et al (2020) further demonstrated that only very small amounts of VirE2 could be detected in the nucleus in the presence of VirD2 and T-strands, solving the conundrum of conflicting results from different laboratories.…”
Section: Vire2 Must Localize To the Plant Cytoplasm To Facilitate Transformationmentioning
confidence: 99%
“…1 ). Previously, PhiLOV has been used to tag T3Es of animal pathogens to monitor effector secretion and translocation 52 and to visualize translocation and localization of A. tumefaciens virulence proteins 53 . In another study, a split GFP system was used to monitor the secretion of T3Es of P. syringae and R. solanacearum 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the subcellular localization of VirE2 remains controversial. Early reports demonstrated nuclear localization of VirE2 (Citovsky et al, 1992), but other studies from several laboratories indicated that VirE2 localizes in the cytoplasm (Grange et al, 2008; Gelvin, 2010; Roushan et al, 2018). A recent report claimed that a small amount of VirE2 can enter the nucleus, but only in the presence of VirD2 and T-strands (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%